MODEL PEMBELAJARAN KOPERTIF TIPE NUMBERED HEADS TOGETHER DALAM PENINGKATAN MOTIVASI BELAJAR IPA SISWA MTsN 1 NAGAN RAYA - Roslidar Roslidar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
Learning motivation is needed so that students are more focused in following lessons, including science lessons. The Numbered Heads Together (NHT) learning model is applied to increase students' learning motivation. Therefore, this discussion aims to determine the increase in students' learning motivation by using the NHT type cooperative learning model and the focus of this research is to increase motivation and differences in motivation before and after the application of NHT. Therefore, the discussion of this thesis aims to determine the increase in learning motivation of MTsN 1 Nagan Raya students by using the NHT type cooperative learning model and the focus of this research is to increase motivation and differences in motivation before and after the application of NHT. This research is a Classroom Action Research (CAR) with a quantitative approach. Data was collected by distributing questionnaires before and after learning. The data obtained from the questionnaire were analyzed by using the Paired Samples Test. The results of this study indicate a significant difference in students' learning motivation towards science lessons before and after the application, the score of student learning motivation is low before the application of NHT with an average value of 36.26. However, there was an increase in student motivation scores after the application of NHT with an average score of 70.24 which was categorized as high.Keywords: Model Numbered Heads Together (NHT), Science Learning